Schindler's list - Keneally, Thomas frey50 (New York : Simon and Schuster, 1993)
A mature novel that is a fictionalized treatment of the life of the German industrialist who saved the lives of many Jews during World War II. Schindler's List is a remarkable work of fiction based on the true story of German industrialist and war profiteer, Oskar Schindler, who, confronted with the horror of the extermination camps, gambled his life and fortune to rescue 1,300 Jews from the gas chambers. Working with the actual testimony of Schindler's Jews, Thomas Keneally artfully depicts the courage and shrewdness of an unlikely savior, a man who is a flawed mixture of hedonism and decency and who, in the presence of unutterable evil, transcends the limits of his own humanity.
"A Touchstone Book."
Keywords: Schindler, Oskar -- 1908-1974; Righteous Gentiles in the Holocaust -- Poland -- Krakow; World War, 1939-1945 -- Jews -- Rescue -- Poland -- Krakow; Holocaust, Jewish (1939-1945) -- Poland -- Krakow; Biographical fiction; War stories